The Role of The Teacher Working Group (KKG) on The Professionalism of Islamic Religious Education Teachers in The Independent Curriculum - Mujtahid, Mujtahid; Assidiqi, Ali Hasan; Sadiyah, Dini; Sidiq, M Umar (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED), 2024)
The Independent Curriculum is one of the updates given by the government to be able to overcome educational challenges and problems so that Indonesia is more advanced. However, it is undeniable that in addition to having positive values, it also has negatives, especially for teachers who have entered old age and teachers who still do not understand in detail because of changes such as activities, devices, etc., including for Islamic religious education teachers to achieve professional teachers. This is because they become teachers who teach not only focusing on the world but also the hereafter. One of the solutions is the role of the Teacher Working Group (KKG) which must be optimized so that it has benefits. For this reason, the researcher is interested in researching the role of KKG in Group IV in fostering professional Islamic religious education teachers. The method used is a type of qualitative research with the collection of interviews, observations and documentation. The results obtained were that there were two KKGs in group IV of Lowokwaru District. First, the KKG Group IV which is focused on all elementary school teachers, including Islamic religious education teachers. Second, the KKG Group IV Islamic Religious Education (PAI) which focuses on PAI subjects only. In both activities, they have the same activities but several different things such as time, management composition, main activity programs and others, the goal is the same, namely to be able to make teachers understand the independent curriculum, including making teachers professional.  Of the various activity programs, almost all activities were carried out well, then also had an impact on Islamic religious education teachers, such as: better understanding the teacher's duties to students, understanding the independent curriculum starting from the syllabus, teaching modules, projects to strengthen the Pancasila learning profile and others. All Islamic religious education teachers feel helped by the existence of the KKG to make teachers professional both in their teaching tools and activities. So with this, the role of the KKG is very positive so that this also supports data from other studies that state that the KKG has the ability to reach 79.00% of the 80 teachers who fill in the research data.